Cele sporządzania sprawozdań finansowych w praktyce Niemiec i Wielkiej Brytanii a standardy międzynarodowe - Theile, Carsten; Stahnke, Melanie (Aims of Making Financial Statements in German and Great Britain Practice versus International Standards, 2005)
Aims and means which are at disposal of a subject decide about keeping of accounting. Thus law regulations have to be correlated with its aims. In the light of the theory the financial accounting has three aims. First it is the basis to calculate a financial outcome, second it enables to calculate the taxation base and third it is to help the users of financial statements to take economic decisions. Against a background of present regulations in MSSF, MSR and GAPP, the article presents aims and structure of German and British accounting regulations, focusing attention on the loss of assets value and difficulties in assessing the reclaiming value. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 301-315